Frequency of neoplasms in canines 0 to 5 years of age diagnosed in the Laboratory of Veterinary Histopathology of the National University of San Marcos (2003-2014) - Chang H., Ghiis (2017)
A total of 4701 canine protocols, processed at the Laboratory of Histopathology of the Faculty of Veterinary Medicine of the National University of San Marcos (Lima) during the period 2003-2014 were evaluated to determine the frequency of types of cancer diagnosed by histopathology and in the case of the transmissible venereal tumor (TVT) by cytology. There were 3480 cases of neoplasms, of which 554 (11.8%) belonged to canines from 0 to 5 years of age. The 4-5 years old dogs (261 cases, 47.1%) and the male dogs (333 cases, 60.1%) had the highest number of neoplasms. The benign neoplasms predominated with 279 cases (50.4%), with TVT being the most frequent neoplasia of this group and of the general count with 94 cases (33.7%). The most frequent malignant neoplasm was rhabdomyosarcoma, with 47 cases (17.1%).